Digital Transformation in Primary Education - Kamila, Octavia Nuril; Manafe, Leonard Adrie; Shobikin, Shobikin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study investigates the introduction of digital technology in primary school administration, specifically at SD Muhammadiyah 3 Ikrom Wage. The aim is to make education management more efficient and transparent, while improving service quality. The researcher collected data using traditional methods—observation, interviews, and document analysis—and analysed them using descriptive qualitative methods. Field findings indicate that digital systems do reduce time and improve communication, but they still face challenges such as infrastructure limitations, low digital literacy, and resistance from some teachers. On the positive side, transformational school principals provide regular training and invite parents and other stakeholders to participate. To accelerate the digitalisation process, schools need to improve internet connectivity, equip educators with adequate skills, and hope for continued policy support. A well-functioning digital administrative system, in turn, has the potential to boost overall educational performance and service quality.